Analysis of Advertising, Sales Promotion, and Public Relation on Coffe Purchasing decisions in The Sragen Coffe Garage During the Covid-19 Pandemic - Endang Brotojoyo; Veronica Titi Purwantini (Common Publisher, 2020)
Purpose this study is to empirically determine the effect of advertising, sales promotion and public relations partially and simultaneously on purchasing decisions. The sample in this study amounted to 100 respondents using the Slovin formula and the sampling technique of the Convinience Sampling method. Types and sources of data obtained from primary data sources and secondary data sources. Data was collected by making a questionnaire regarding advertising, sales promotion, public relations and purchasing decisions. The results of that partially and simultaneously the effect of advertising, sales promotion and public relations has a positive and significant effect on purchasing decisions. The results of the calculation of the coefficient of determination show that the variables of advertising, sales promotion and public relations can explain the purchasing decision variable by 77.2%, while the remaining 22.8% is influenced by other variables not included in this study, such as location, personal sales and publications.